An evaluation of internet financial reporting on specific Malaysian economic sectors - Turmin, Siti Zaidah; Osman, Mohamad Noor Hisham (Human Resource Management Academic Research Society, 2020)
Internet Financial Reporting (IFR) is the communication process between the corporate sector and its stakeholders, via the medium of the Internet. This study was conducted to examine the factors inspiring the extent of IFR practices by companies in specific Malaysian economic sectors. The sample consisted of fifty companies practising IFR from the sectors of plantations, trading and services, consumer products, industrial products and technology. Data was collected through the websites of the sampled companies. The results of multiple regressions have revealed that the independent variable of profitability, as measured by the return on equity, as well as the independent variable of the type of auditor, were found to positively and significantly inspire the extent of IFR practises among the sampled companies. The factors of leverage, liquidity, industry type and firm size were, however, found to be insignificant. The study has made a significant contribution towards the knowledgebase of IFR issues in the context of emerging economy countries which have previously experienced very limited study, as well as raising implications for users and auditors.